Bedrock identification using refraction seismic method in establishment location of Hospital Education Sebelas Maret University - Murteza Nur Isnani Rahmawati; Budi Legowo; Artono Dwijo Sutomo (Department of Physics, Sebelas Maret University, 2016)
A research of refraction methods in estabilishment location Hospital Education Sebelas Maret University has been done on October 31 2012 with P.A.S.I Seismograph Mod. 16S24 seismic refraction instruments with 24 geophone. This research in order to determine the depth of bedrock in the estabilishment location hospital education Sebelas Maret University. In this data acquisition, the travel time data was a distance function. Processing and interpretation data used Intercept Time Method. Intercept Time Method used value of intercept time concept from travel time curve. This interpretation which resulted P wave velocities and layer rocks thickness in three line which scattered in area of survey. The result was that we were able to obtain bedrock having the depth of 4 meters until 9 meters and heaving spreading velocity 1079 m/s – 1182 m/s is interpreted as talus deposits, sandstone, clay, loam, loess, sand and gravel.